Pengaruh pemberian kurma terhadap produksi asi pada ibu nifas - Agustina, Melina; Yuviska, Ike Ate; Putri, Ratna Dewi; Evayanti, Yulistiana (JOURNAL OF Community Health Issues, 2023)
ABSTRACT The coverage of exclusive breastfeeding has only reached 41.9%, this can contribute to maternal mortality (MMR), infant mortality (IMR) and nutritional status of toddlers. The provision of exclusive breastfeeding 0-6 months in Lampung province in 2016 is still low at 40.17%, while in Bandar Lampung City in 2016 the coverage of exclusive breastfeeding is 41.9%. Based on the pre-survey results that researchers have done at BPS Nurhasanah, STr, Keb Bandar Lampung in 2019 in February 2019, there are 48 postpartum mothers, of which 10 postpartum mothers, where 6 (60%) of postpartum mothers are not smooth , and 4 (40%) postpartum ASI mothers smoothly. The purpose of this study is to know that there is an effect of giving dates to breast milk production in postpartum mothers in Bps Nurhasanah, Str, Keb Bandar Lampung in 2019. Quantitative Research Type, the research design is a quasi experimental design with a pretest-posttest design with a control group. The population of all postpartum mothers was 48 people, a sample of 30 people 15 people as the intervention group 15 people as a control group. With purposive sampling sampling technique. Analyze data with T-test Independent. The results showed that the average ASI production before the intervention was 68.33 ml, the average milk production after the intervention was 105.00. ml whereas in the control group the average milk production before intervention was 68.67 ml and the average milk production after the intervention was 80.00 ml. It is known that there is an effect of giving dates to breast production in postpartum mothers at BBP Nurhasanah, Str, Keb Bandar Lampung in 2019. The results of the t test are p value 0,000 <α (0.05). It is recommended for health workers especially midwives to recommend to postpartum mothers to consume dates so that their milk production is smooth. Keywords: Dates, Breast Milk Production Cakupan ASI ekslusif baru mencapai 41,9%, hal ini dapat berkontribusi terhadap angka kematian ibu (AKI), angka kematian bayi (AKB) dan status gizi Balita. Pemberian ASI eksklusif 0-6 bulan di propinsi Lampung Tahun 2016 masih rendah yaitu 40,17 %, sementara di Kota Bandar Lampung Tahun 2016 cakupan ASI ekslusif sebesar 41,9%. Berdasarkan hasil prasurvey yang telah peneliti lakukan di Di BPS Nurhasanah, STr,Keb Bandar Lampung Tahun 2019 pada Bulan Februari Tahun 2019, terdapat 48 ibu nifas, dimana dari 10 ibu nifas, dimana 6 (60%) ibu nifas tersebut produksi ASI nya tidak lancar, dan 4 (40%) ibu nifas ASI nya lancar. Tujuan dari penelitian ini adalah diketahui ada Pengaruh Pemberian Kurma Terhadap Produksi ASI Pada Ibu Nifas Di Bps Nurhasanah, Str,Keb Bandar Lampung Tahun 2019. Jenis Penelitian Kuantitatif, rancangan penelitian pendekatan quasi eksperimental desain dengan rancangan pretest-posttest with control group. Populasi seluruh ibu nifas sebanyak 48 orang, sampel sebanyak 30 orang 15 orang sebagai kelompok intervensi 15 orang sebagai kelompok kontrol. Dengan teknik sampling purposive sampling. Analisa data dengan uji T-test independent. Hasil penelitian menunjukan rata-rata produksi ASI sebelum intervensi sebesar 68.33 ml, rata-rata produksi ASI setelah intervensi sebesar 105.00. ml sedangkan pada kelompok kontrol rata-rata produksi ASI sebelum intervensi yaitu sebesar 68,67 ml dan rata-rata produksi ASI setelah intervensi adalah sebesar 80.00 ml. Diketahui Ada Pengaruh Pemberian Kurma Terhadap Produksi Asi Pada Ibu Nifas di BBP Nurhasanah, Str,Keb Bandar Lampung Tahun 2019. Hasil uji t didapat p value 0,000 < α (0,05). Disarankan bagi tenaga kesehatan khususnya bidan agar menganjurkan kepada ibu nifas untuk mengkonsumsi kurma agar produksi ASI nya lancar